How sports lead to the physical fitness in China? - Chai Zhongxue (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The objective of this study is to address the role of sports in physical fitness. To achieve this objective, the relationship between sports, stress control, physiological motivation and physical fitness was examined. To check these relationships, seven hypotheses were proposed. Data were collected from players related to the various games in China such as football, hockey, basketball etc. The primary data were collected with the help of questionnaire. Partial Least Square (PLS) was used for data analysis. It is found that; sports have positive effect on physical fitness. Sports also has positive effect on stress control. Furthermore, sports have positive effect on physiological motivation. The stress control has positive effect on physical motivation. Finally, physiological motivation also has positive effect on physical fitness. Therefore, this study shows that sports has important contribution towards physical fitness. Sports increases the physiological motivation with the help of stress control and physiological motivation. Both the stress control and physiological motivation has positive role to transfer the effect of sports on physical motivation.